Trait-mediated shifts and climate velocity decouple an endothermic marine predator and its ectothermic prey - L. H. Thorne (Nature Portfolio, 2021)
Abstract Climate change is redistributing biodiversity globally and distributional shifts have been found to follow local climate velocities. It is largely assumed that marine endotherms such as cetaceans might shift more slowly than ectotherms in response to warming and would primarily follow changes in prey, but distributional shifts in cetaceans are difficult to quantify. Here we use data from fisheries bycatch and strandings to examine changes in the distribution of long-finned pilot whales (Globicephala melas), and assess shifts in pilot whales and their prey relative to climate velocity in a rapidly warming region of the Northwest Atlantic. We found a poleward shift in pilot whale distribution that exceeded climate velocity and occurred at more than three times the rate of fish and invertebrate prey species. Fish and invertebrates shifted at rates equal to or slower than expected based on climate velocity, with more slowly shifting species moving to deeper waters. We suggest that traits such as mobility, diet specialization, and thermoregulatory strategy are central to understanding and anticipating range shifts. Our findings highlight the potential for trait-mediated climate shifts to decouple relationships between endothermic cetaceans and their ectothermic prey, which has important implications for marine food web dynamics and ecosystem stability.